THE HEALTH OF MEN DEPRIVAD OF LIBERTY IN BRAZIL - Cristo, Micheli; Diniz, Michele Lopes; Conceicao, Vander Monteiro da; Furlan de Leo, Marcela Martins [UNESP]; Santos, Jeferson Araujo dos; Abrantes de Oliveira Simoneti, Rafaela Azevedo (Univ Federal Estado Rio De Janeiro, Programa Pos-graduacao & Enfermagem, 2020)
Objective: to analyze the national scientific productions about men's health care in the prison context. Method: integrative literature review following six steps. The searches were performed in a database - Latin American and Caribbean Health Sciences Literature and in the online journal portal - Scientific Electronic Library Online. Studies from the last ten years, published in Portuguese and in full were included. The analysis and exposition of the results were through the descriptive approach. Results: The search resulted in 546 articles in both databases. After analyzing the inclusion and exclusion criteria, nine studies were included. After reading and analyzing these studies, four thematic categories were constructed. Conclusion: What is approached and defended in public health policies is not put into practice. Health professionals and security agents act in a simple assistance, without humanization, and without preventive health measures.
Keywords: Men; Prisons; Nursing; Men's Health